Implementasi Ruqyah Syar’iyah sebagai Alternatif Psikoterapi dalam Kajian Psikologi Islam - Arni Arni (Jurnal Studia Insania, 2021)
Ruqyah Syar'iyyah is an Islamic healing that uses recitation of the holy Koran, dhikr and prayers. Diseases that can be cured through ruqyah syar'iyyah with the permission of Allah are physical and mental illnesses or physical and spiritual diseases, in other terms are physical or psychological illnesses. The basis for this Islamic healing is found in the Koran and the hadiths of the prophet. Even though there is a basis, the attitude of the Muslims towards ruqyah is divided into three parts, namely ifrath, tafrith and mu'tadil. For patients who suffer from the law, asking for meruqyah is only permissible, while peruqyah for circumcision is to help people who ask for help. The scholars agree that the use of this ruqyah with the holy Koran verses and believe that humans are only as intermediaries, the problem of healing is the permission of Allah SWT. Rasulullah practiced three types of divine medicine, namely Ruqyah Sayar'iyyah, Thabi'iyyah and Al-Jam'u baina huma. These three are summarized in a system called Thibbun Nabawi. This Ruqyah with Allah's permission makes a sick person become healthy, or a person who was originally unconscious becomes conscious. In the past, in our area it was known as batatamba, which is to treat illnesses to healers who use the holy Koran, dhikr and prayers. Now the term ruqyah syar'iyyah is popular. Nowadays, ruqyah is practiced or practiced on TV, Youtobe and in certain places that provide official medical treatment. Apart from ruqyah for sick people, there are also people who are healthy, conscious and suspect that they have jinn, so they ask for diruqyah. In the end, he was unconscious as if he was possessed by spirits, and some even vomited and urinated after being recited by the peruqyah recitation of the ruqyah. This situation collides with the aim of ruqyah which is to heal a sick person or awaken an unconscious person. Not a person who is conscious of being forced to become unconscious (a kind of trance). If he died at this time, of course he would forget Allah.